Use the seeds of chia seeds as ingredient of milled half-finished foodstuffs - Golembovska, N. V.; Slobodyanyuk, N. M. (НУБіП України, 2018)
There are given results of sensory analysis of flavor and some other properties of milled masses of freshwater fish enriched by the non-traditional raw material (seed of chia seeds). The conclusion on positive effect on properties of proposed compositions over those ones of the standard sample of force-fish was made on comparing of base profiles of their basic properties. The cutlets made of mass modified by vegetative ingredient had the plastic and dense consistency on their cut. The positive results of their organoleptic analysis evidenced expediency of adding of proposed vegetative ingredient to milled mass of fish. The criteria proved such conclusion were general expression of taste, aroma and harmonicity of flavor of cutlets made of mixes of developed composition. It was shown experimentally that adding of vegetative raw materials in the mix permits to increase its nutritional value. Absence of negative effects followed after adding of seeds of chia seeds into the minced fish mass permits us to recommend it for consumption as the product of dietetic destination.
Використання насіння чіа в якості інгредієнта подрібнювання напівфабрикатів продуктів харчування
Наводяться результати сенсорного аналізу смаку і деякі інші властивості подрібненої маси прісноводних риб збагаченого нетрадиційної сировини (насіння Насіння чіа). Висновок на позитивний вплив на властивості запропонованої композиції за ті стандартного зразка форс-риба був зроблений на порівнянні базових профілів їх основні властивості. Котлети з маси модифікованих рослинних інгредієнтів мають пластику і щільної консистенції на свою частку. Позитивні результати органолептичного аналізу свідчать про доцільність додавання запропонував рослинний інгредієнт для розмолотої маси риби. Критерії довів такого висновку було загальне вираження смаку, аромату і гармонійність смаку котлети з суміші розробленого складу. Експериментально було показано, що додавання рослинної сировини в суміші дозволяє підвищити його поживну цінність. Відсутність негативних наслідків після додавання насіння чіа в рибний фарш мас дозволяє нам рекомендувати його для вживання в якості дієтичного продукту призначення.
Keywords: Fish cutlets; vegetative raw materials; chia seeds; semi-finished products; organoleptic testing; sensory characteristics; flavor; taste; profilogram; рибні котлети; рослинна сировина; насіння чіа; напівфабрикат; органолептичні випробування; органолептичні показники; аромат; смак; профілограм